Product Development of Canarium Odontophyllum as Kembayau Exotic Fruit Sauce - Mohd. Nazri Abdul Rahman; Nur Azimah Mohammed Thajudin (UMK Publisher, 2015)
Canarium Odontophyllum or known as Kembayau and/or Dabai (Dacryodes rostrata f. cuspidate) is an underutilized exotic (indigenous) fruit that can be found in Borneo region particularly Sabah, Sarawak, Brunei and Kalimantan tropical forest. Kembayau is less popular compared to Dabai fruit due to the taste and thickness of flesh. It is rich in minerals, proteins and carbohydrates with milky taste. This study was done to determine the suitability of Kembayau fruit as a sauce. Three formulations, F3, F5 and F8 out of nine were chosen after going through BIB ranking test and F8 then chosen through hedonic test for proximate analysis, microbial storage study and quality sensory. F8 contains 45% Kembayau fruit puree, 30% sucrose, 18% water, 1.53% modified corn starch, 0.1% xanthan gum, 4% margarine, 0.9% salt, 0.4% citric acid and 0.07% sodium benzoate. As result, Kembayau fruit sauce contains 60.43±0.40 moisture, 0.50±0.10 ash, 0.75±0.03 fat, 1.40±0.07 protein, and 0.92±0.02 crude fibre and 35.50±0.04 carbohydrates. Physicochemical shown sample had pH at 3.15±0.10, 34.00±0.01 °Brix, viscosity at 24.42±0.10 cP and L*a*b* was at 39.75±0.18, 6.12±0.07, and 12.42±0.08 respectively. From the view of storage studies, at eight week of storage, sample are contains bacteria and yeast at 3.11x102 cfu/ml and 3.55x102 respectively at concentration 10-1 . Consumer test shows that Kembayau sauce is acceptable among consumers. As conclusion, Kembayau is a potential exotic fruit to be studied for the food product development.